Dietary diversity and biofortification: Closer than you think - Kennedy, Gina; Moursi, Mourad (International Food Policy Research Institute, 2015)
Some 2 billion people suffer from hidden hunger caused by infections and diets lacking in essential micronutrients such as vitamin A, iron, and zinc. This is particularly the case in the developing world, where diets mainly consist of starchy staples and not enough nutrient-rich foods such as fruits, vegetables, beans and pulses, and animal source foods. But what if those food staples that people eat regularly were made to work toward better nutrition? And how does that fit with the need for dietary diversification?